Early warning of Diaporthe infection in kiwifruit soft rot by plasmonic dimer-enhanced Raman spectroscopy - Ting Yu; Huanhuan Li; Baomei Zhou; Kui Liu; Hao Jiang; Min Xu; Mengke Su; Yongsheng Liu; Min Miao; Honglin Liu (iScience, 2022)
Summary: Diaporthe genus is the dominant pathogens of kiwifruit soft rot with long incubation period and rapid onset and very hard to detect in advance. It is of great significance to develop point-of-care tests for disease prevention and field management. Here we screen a pair of genus-level primers for constructing plasmonic dimer Rayleigh/Raman spectroscopy, which enables rapid, specific, and sensitive detection of Diaporthe genus in real kiwifruits. Dark-filed Rayleigh scattering clearly visualizes the target-induced dimer assembly of nanoprobes. Plasmonic dimer-enhanced Raman spectroscopy has high specificity for 12 common isolates of Diaporthe genus in one batch samples with highly accurate results and much higher sensitivity than polymerase chain reaction (PCR). It realizes the recognition of Diaporthe infection at an early stage of 24 h when the kiwifruits do not have any noticeable symptoms. It demonstrates a bright prospect of point-of-care tests for early warning of kiwifruit soft rot infection and quality control.